Position Change of the Moon to showing the Lunar Mansion's Pattern - A. Sukwisoot (2018)
© Published under licence by IOP Publishing Ltd. This research was conducted to find out the pattern of the lunar mansions from the position change of the Moon. These positions were called as the lunar mansions. The lunar mansions have 27 groups with important 27 fixed stars. The Moon's position was calculated from nearby stars by cosine formula. The smallest angular separation between the Moon and the fixed stars was the lunar mansion of the day. The graph relates with the date from 2011-2030 and the lunar mansions was showed the lunar mansion's pattern. It was found that the lunar mansion's pattern was a linear equation as M = (0.9882x + 15.4192) ± 0.6910.